Analysis of Publications on Earthquake Research in Architecture Category and Analysis with R Studio-Biblioshiny Software - Lale Karataş; Emine Banu Burkut; Murat Dal (Journal of Architectural Sciences and Applications, 2023)
The purpose of this research is to examine the publications focusing on earthquakes in the category of architecture (web of science). The data of the research was analyzed with the Biblioshiny software program. This software program makes a bibliometric analysis on which topics and concepts earthquake research focuses. In addition, images and frequencies of publications related to architecture and earthquakes were revealed. The data of the research was collected between 1-15 July 2023. Results for Architecture (WoS Categories) AND earthquake* (Topic) OR earthquake AND architecture (Topic) OR earthquake AND house (Topic) OR earthquake AND structure (Topic) OR earthquake AND damage (Topic) OR earthquake AND city (Topic) OR earthquake AND urban (Topic) and Türkiye (Countries/Regions). Data were collected with keywords in the Web of Science database. According to the research findings, there are 1033 publications and in the country/region category (Türkiye), 83 publications are accessed. The most used words in the publications are earthquake, urban transformation, Istanbul, seismic, retrofit, assessment, structural, urban, damage, buildings and performance.